The prevalence of depression, anxiety, and stress among high school adolescent's children in public and private schools in Rangareddy district Telangana state: A cross-sectional study - R Kranthi Kumar; G Aruna; Nandini Biradar; Kola Srikanth Reddy; M Soubhagya; S A Sushma (Journal of Education and Health Promotion, 2022)
BACKGROUND: The depression, anxiety, and stress is a major educational problem among students all around the world. The purposes of this study were to determine the depression, anxiety, and stress among the high school adolescent children in public and private schools in Rangareddy district, Telangana state. MATERIALS AND METHODS: The present study was a cross-sectional study. The study sample considered 120 children from private schools and 259 children from public schools were studied. The study tool used was a questionnaire containing DASS (Depression, Anxiety, and Stress scale and sociodemographic characteristics. The data were expressed as proportion and mean values (Analysis of variance, independed t-test, and Pearson correlation) spatially tests were used at a significance level of P < 0.05). >RESULTS: The overall prevalence of depression in children from the public school was found to be only 5%, that of anxiety was 20.8%, and that of stress was 15.8%; the overall prevalence of depression in children from private schools was found to be 1.9%, that of anxiety was 20.5%, and that of stress was 20.1%. CONCLUSION: In both schools, anxiety and atress were found to be more among study participants. Depression was observed to be less. But if they have more anxiety and stress and if not taken proper care at this point of time, it might get converted into a state of Depression.